A Key to Entrepreneurship Promotion:A 3D Approach - Waghodekar, P. H. (Journal of Engineering Education Transformations, 1990)
This paper briefly presents the essentials of entrepreneurship promotion. For example, areas, like, types of entrepreneurs, qualities of entrepreneurs, etc, have been highlighted It has been proposed that the education system, industries and Government are the three dimensions which can help generate a conducive social environment thereby promoting entrepreneurship cult in the masses. It is believed that this paper can be a thought provoking one for furthering the entrepreneurship promoting spirit in India.